Kolaborasi Pemerintah Kota Serang dan Ormas Islam dalam Memberantas Prostitusi di Alun-Alun Kota Serang - Sherly Melinda; Delly Maulana; Fikri Habibi (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2020)
This study discusses how the Serang City Square as a public open space is abused by prostitution as a place for approval of prostitution transactions. These conditions make the City Government of Serang do various ways to allow the condition of the City Square of Serang which has been abused by parties related to prostitution. When the government has not been able to deal with the problem of prostitution itself, then to facilitate the handling of prostitution, the government collaborates with other parties, namely Islamic Organizations that are considered capable of assisting the City Government of Serang in eradicating prostitution in Serang City Square. However, at the time of the collaboration between the Serang City Government and the Islamic Organizations, it had not been running optimally because there were some collaborations between one of them which was not going well with good communication between the best institutions and the Islamic Organizations in eradicating prostitution. This is because the government considers that Islamic Organizations do not have the authority to eradicate prostitution. Indeed, the role of Islamic Organizations is only as a companion and to remind the government.